2021
DOI: 10.5455/aim.2021.29.176-181
|View full text |Cite
|
Sign up to set email alerts
|

The potential of A. Muricata Bioactive Compounds to Inhibit HIF1 and #945; Expression Via Disruption of Tyrosine Kinase Receptor Activity: an In Silico Study

Abstract: Background: Cancer is a debilitating disease that is on the increase in both developed and developing countries. The plant extract of A. muricata have been known to have a variety of anticancer effects, including anti-angiogenic potential. An in silico study is needed as a preliminary study to understand the mechanism underline this process. Objective: The aim of this study was to investigate the potential of the bioactive compounds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that kaempferol might be involved in NF- κ B signaling pathway to inhibit the expression of the major proinflammatory cytokines, including IL-17A and TNF- α , and decrease the percentage of IL17A + CD4 + T cells in the imiquimod (IMQ)-induced psoriatic mouse model [ 29 ]. In addition, kaempferol, genistein, and glycitein disrupt interleukin (IL)-6R, toll-like receptor (TLR)-4 and their respective ligands interaction to hinder the expression of HIF-1, which is associated with the phosphoinositide 3-kinases (PI3K)/Akt signaling pathway [ 30 ]. Relevant studies have found that TLRs are transmembrane pattern recognition receptors that play an important role in the detection and defense of microbial pathogens in natural immunity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that kaempferol might be involved in NF- κ B signaling pathway to inhibit the expression of the major proinflammatory cytokines, including IL-17A and TNF- α , and decrease the percentage of IL17A + CD4 + T cells in the imiquimod (IMQ)-induced psoriatic mouse model [ 29 ]. In addition, kaempferol, genistein, and glycitein disrupt interleukin (IL)-6R, toll-like receptor (TLR)-4 and their respective ligands interaction to hinder the expression of HIF-1, which is associated with the phosphoinositide 3-kinases (PI3K)/Akt signaling pathway [ 30 ]. Relevant studies have found that TLRs are transmembrane pattern recognition receptors that play an important role in the detection and defense of microbial pathogens in natural immunity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calpain-1-mediated hypoxia-induced oxidative stress and apoptosis involve a variety of protein molecules, among which hypoxia inducible factor-1 α (HIF-1 α ) may play a crucial role. Studies have shown that calpain-1 is involved in many physiological and pathological phenomena [ 42 ], including the disruption of HIF-1 α by hypoxia [ 43 ], and calpain-1 activation accelerates HIF-1 α signal accumulation [ 44 ]. Therefore, we investigated the effect of AS-IV on the inhibition of the calpain-1/HIF-1 α pathway in hypoxia-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our objective was to investigate the potential of CDs to form inclusion complexes with curcumin or THC and to examine their effects on VEGF activity using in silico analysis. The advantages of in silico analysis include the ability to obtain optimal physical and chemical properties of ligands or drug compounds and the time efficiency derived from the use of various software simultaneously (Dewi et al 2021;Wadood et al 2013;Wahyuningsih et al 2022). The primary aim of this study was to assess the potential of curcumin and THC inclusion complexes in inhibiting VEGF activity.…”
Section: Introductionmentioning
confidence: 99%